KAJIAN KONSEP EKOLOGIS PADA GEDUNG PERPUSTAKAAN PUSAT UGM - Alifiano Rezka Adi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2017)
Title: The Study of Ecological Concept in the Central Library of Gadjah Mada University Ecological architecture becomes one of the concept as well as solutions in the building design which minimizes environmental damages and maintains the quality of human life. The central library of Gadjah Mada University in Yogyakarta is used as the research object to rate its ecological level. This study uses a quantitative method to rate its ecological level based on the ecological design principles of Sim Van der Ryn such as ecological accounting, design with nature, and making nature visible. The assessment parameters are based on some references such as the greenship of GBCI, the principles of tropical architecture, and the principle of building accessibility. The results showed that generally, the library has applied ecological concept well through some strategies such as extensive greening, energy efficiency, adequate natural lighting, slim building masses, shading elements, and some facilities for the difable. Some measurements are done to find out the ecological performance of the building such as energy efficiency by 39.17%; daylighting 300 lux at 60.67% of indoor area, visualization of solar radiation reception, and OTTV value by 19,85 watt/m2. However, there are some necessary evaluations such as leakage on the ceiling or the application of greenroof that can be further optimized.